Museum and education. Museum pedagogics. Museum specialist as an educator - Kossova, Irina (Knygotyra, 2003)
Recent times have brought into being a new concept of edutainment. More and more museum is valued and evaluated not only as a provider of knowledge but also as a specific place for experience, entertainment and education. Such attitude towards a museum forms the basic concepts of the museum pedagogics which, in its own place, constitutes the theoretical framework of the cultural and educational activities of a museum.In Russia, as well as in Germany, United Kingdom, Canada, USA and other countries, the development of the museum pedagogics is determined by the cultural policy and strategy defining the use of the museum educational potential.A creative laboratory Museum pedagogics was formed in 1990 within the Academy of Continuing Education for the Cultural Workers in Moscow, Russia. The laboratory serves as a dynamic model for educating museum educators who are in charge of cultural and educational activities of a museum.Thanks to the successful and open activities of this laboratory as well as to many conferences in regional museums, interesting educational and amusing programmes targeted at various publics appeared in Russian museums.
Keywords: -